Identification of mechanical properties of weld joints of AlMgSi07.F25 aluminium alloy - P. Kopas; M. Blatnický; M. Sága; M. Vaško (Metalurgija, 2017)
The aim of this paper is to present the analysis of selected mechanical properties of weld joints of AlMgSi07.F25 aluminium alloy. We will focus on the influence of the test bar neck shape on the tensile strength characteristics and the course of hardness in the weld joint cross-section. For the welding process using TIG (Tungsten Inert Gas) technology we considered AlSi5 as the additive material. This paper also includes a short study of numerical modelling of the test bar welding.